Inferioritas Pada Siswa Smp dan Mts Di Pulau Ternate - Musawwir; Zubair, Arie Gunawan Hazairin; Inayah, Nurul (Program Studi Bimbingan dan Konseling Islam IAIN Palu, 2021)
This study aims to describe the inferiority that exists in junior high school students in Ternate Island. Inferiority is due to feeling that there is a deficiency in yourself or an imperfection in an individual's life. This feeling will encourage someone to be insecure and tend to feel fail. The method used in this research is descriptive quantitative approach. The sample that will be involved in this research is around 648 students of SMP / MTs at Ternate city. This sample size was obtained by dividing the sample size of 24 students per school, 8 students per batch (grades 1-3), consisting of 4 boys and 4 girls. The variables will be measured using an inferiority scale instrument compiled by researchers based on the inferiority dimensions proposed by Adler, namely, Feeling of being below, Feeling of feminity, and Feeling of insecurity (feeling insecure). This scale consists of 48 items, with 24 favorable items and 24 unfavorable items. The results showed that there were 36 respondents (8%) who had an inferiority score in the very high category, 98 respondents (22%) were in the high category, 161 respondents (37%) were in the medium category, 123 respondents (28%) were in the low category, and 24 respondents (5%) are in the very low category. These results indicate that inferiority is a situation faced by students but can still be overcome with various approaches